2014
DOI: 10.5937/fmet1401056p
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of Shliomis model based magnetic squeeze film in rough curved annular plates with assorted porous structures

Abstract: In present theoretical investigation, the effect of Shliomis model based

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…It was realised that the magnetization could also reduce the adverse effect of surface roughness up to some extent when suitable values of slip parameter were in place. Then Patel and Deheri reported the FFs lubrication of a squeeze film in rotating rough porous curved circular plates and rough curved annular plates . The stochastic modelling of transverse roughness was employed in the two literatures.…”
Section: Ferrofluids Lubrication Based On Three Flow Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was realised that the magnetization could also reduce the adverse effect of surface roughness up to some extent when suitable values of slip parameter were in place. Then Patel and Deheri reported the FFs lubrication of a squeeze film in rotating rough porous curved circular plates and rough curved annular plates . The stochastic modelling of transverse roughness was employed in the two literatures.…”
Section: Ferrofluids Lubrication Based On Three Flow Modelsmentioning
confidence: 99%
“…Configuration of the curved annular plates bearing system . The bearing consists of two annular plates with each of inside radius b and outside radius a ( a > b ).…”
Section: Ferrofluids Lubrication Based On Three Flow Modelsmentioning
confidence: 99%
“…It was found that the adverse effect of transverse roughness could be overcome by the positive effect of ferrofluid lubrication in the case of negatively skewed roughness by suitably choosing curvature parameters and rotational inertia when Kozeny-Carmans model was used for porous structure. Patel and Deheri (2014d) theoretically analyzed the performance of Shliomis model based ferrofluid lubrication of a squeeze film between curved rough annular plates with comparison between two different porous structures. It was manifest that the effect of morphology parameter and volume concentration parameter increased the load carrying capacity.…”
Section: Introductionmentioning
confidence: 99%
“…It was noticed that the adverse effect of transverse roughness could be overcome by the positive effect of ferrofluid lubrication in the case of negatively skewed roughness by suitably choosing curvature parameters and rotational inertia when Kozeny-Carman's model was deployed for porous structure. [51] theoretically analyzed the effect of Shliomis model based ferrofluid lubrication on the squeeze film between curved rough annular plates with comparison between two different porous structures. It was shown that the effect of morphology parameter and volume concentration parameter increased the load carrying capacity.…”
Section: Introductionmentioning
confidence: 99%